Separated by the same language: Intralingual translation between Dutch and Dutch. - Brems, Elke (Perspectives: Studies in Translatology, 2018)
Flanders and the Netherlands have a long history of intralingual translation. By looking at the different aspects of this intralingual translation we can gain insight into the evolving power relations between both regions. In the long nineteenth century [1800-1914] and the decades after the Second World War the Netherlandic Dutch norm was prevalent and the Flemings translated their texts into Netherlandic Dutch. During the World Wars there were efforts to change the direction of the intralingual translation in favour of Flemish Dutch. From the 1990s onwards Dutch can be considered a pluricentric language with more or less equal power balance. Intralingual translation often goes both ways: from Flemish Dutch into Netherlandic Dutch and vice versa. The case of Dutch can teach us something about the remit of intralingual translation. In my research I defined seven relevant research angles: the orientation of the translation flows, the field where translation takes place, the medium of the translated language, the stakeholders involved in the translation process, the textual elements that undergo translation, the reception of the intralingual translation and finally, and most importantly, the function of the intralingual translation between languages that do not need translation to understand each other.